2014
DOI: 10.1002/em.21928
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of synthetic amorphous silica nanoparticles in rats following short‐term exposure, part 2: Intratracheal instillation and intravenous injection

Abstract: Synthetic amorphous silica nanomaterials (SAS) are extensively used in food and tire industries. In many industrial processes, SAS may become aerosolized and lead to occupational exposure of workers through inhalation in particular. However, little is known about the in vivo genotoxicity of these particulate materials. To gain insight into the toxicological properties of four SAS (NM-200, NM-201, NM-202, and NM-203), rats are treated with three consecutive intratracheal instillations of 3, 6, or 12 mg/kg of SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 34 publications
0
37
2
Order By: Relevance
“…Interestingly, the same batches of SAS were evaluated for their toxicological effect in previous in vivo or in vitro studies. All four SAS were able to cause lung inflammation in rats by intratracheal instillation, but did not induce any DNA damage, neither in the lung nor in other secondary organs [11]. Similarly, none of them induced DNA damage in different tissues of rats exposed by gavage.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Interestingly, the same batches of SAS were evaluated for their toxicological effect in previous in vivo or in vitro studies. All four SAS were able to cause lung inflammation in rats by intratracheal instillation, but did not induce any DNA damage, neither in the lung nor in other secondary organs [11]. Similarly, none of them induced DNA damage in different tissues of rats exposed by gavage.…”
Section: Discussionmentioning
confidence: 85%
“…Data on the genotoxic properties of SAS, mostly assessed by the comet assay for detecting DNA damage or by the micronucleus assay for chromosomal damage, are however less clear. Generally, positive responses in genotoxicity assays are reported more frequently in vitro [5][6][7][8][9] than in vivo [10][11][12]. However, in vitro results remain quite variable and depend on the physical and chemical characteristics of the SAS and the cell type used.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the same phenomenon in vivo or in vitro. [10][11][12][13][14][15] The mitochondria were observed to be more susceptible than other organelles. In the heart and liver of the SiNP-treated group, more secondary lysosomes were observed than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatotoxicity following intravenous injections of SiNPs has been observed, as expected, because the liver is the primary organ for toxin biotransformation. [13][14][15] Li et al 16 found that acute oral administration of mesoporous SiNPs led to renal damage. Further, the intraperitoneal treatment of amorphous SiNPs probably induced inflammation and DNA damage in the lung, heart, liver, kidney, and brain.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, amorphous SiO 2 nanoparticles caused no morphologic change in Balb/3T3 cells and result in no genetic toxicity, as separately revealed by the Cell Transformation Test and the MN assay (Uboldi et al, 2012). Guichard et al discovered that no significance of DNA injury caused by artificial amorphous SiO 2 nanoparticle as evaluated applying the red blood cell MN test and the normative and Fpg-reformed SCEG on cells derived from broncho-alveolar lavage fluid (BALF), the lungs, sanguis, splenic organ, hepar, keest, and kidneys in rats treated with intratracheal instillations at 3, 24 and 48 h (Guichard et al, 2015). No obvious augment in DNA injury was noted in several tissues (sanguis, splenic organ from femur, hepar, keest, kidney, duodenum, and colon) of amorphous SiO 2 nanoparticles -exposed rats following oral exposure for 3 d using the alkaline and Fpg-reformed comet assays (Tarantini et al, 2015).…”
Section: Introductionmentioning
confidence: 99%